Inspiring, Educating, and Integrating Islamic Values through Community Service Program (KKN) Activities in Timpeh and Kamang Baru Districts - Bella Saprilla; Haliamah Andi Saputri; Andini Regika Putri; Lisa Ningsih; Diva Miftahul Jannah; B.R.E Yunanda (The Future of Education Journal, 2026)
The Community Service Program (KKN) is a form of community service carried out by students as an implementation of the Tri Dharma of Higher Education. This program aims to improve student competency while making a real contribution to the community. The KKN program, implemented in Timpeh and Kamang Baru Districts, carried the theme "Inspiring, Educating, and Integrating Islamic Values." The methods used included social, religious, and educational approaches through various activities such as campus outreach, Ramadan safaris, mutual cooperation, and distribution of takjil (snacks). The results of the activities demonstrated increased public awareness of the importance of education, strengthened spiritual values, and heightened social awareness. This program also provided valuable experience for students in developing communication, collaboration, and problem-solving skills.